Antimicrobial switch therapy in pediatric patients hospitalized by uncomplicated community-acquired pneumonia - Ronaldo MORALES-JUNIOR; Anna C. BARRIENTOS; Raquel M. SCALCO; Aline G. FEVEREIRO; Sulim ABRAMOVICI; Camila C. CAMPIONI (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: To evaluate the duration of intravenous (IV) antibiotic therapy and the practice of switch therapy to oral in the treatment of children aged 2 months to 5 years with uncomplicated severe community acquired pneumonia (CAP) in a pediatric public hospital. Methods: Retrospective, observational and cross-sectional study in which patients who started IV ampicillin treatment were selected. The patients were classified as "eligible" or "ineligible" to undergo switch therapy after 48 and 72 hours of hospitalization according to clinical criteria. Patients with length of stay <or ≥7 days were compared regarding demographic characteristics and antibiotic therapy, considering p <0.05 significant. Results: Eighty-six patients were evaluated, aged 14.4 (IQR: 10.8-22.7) months. The duration of IV therapy was 4 (IQR: 3-6) days; 56% of patients were classified as eligible for switch therapy within 48h and 74% as eligible within 72h. However, only 19 cases (22%) underwent switch therapy at the appropriate time. The main reason for the transition was the accidental loss of venous access (61%). The group with length of stay <7 days had a higher rate of switch and, consequently, shorter IV therapy duration (p <0.01). Conclusion: The switch therapy in the first 48 to 72 hours is not routinely used in the clinical practice in patients hospitalized with CAP. The findings warn of the need for institutional initiatives on this practice, aiming at improving the quality of care with shorter IV therapy duration and impact on length of hospital stay.